2021
DOI: 10.3389/fmicb.2021.633090
|View full text |Cite
|
Sign up to set email alerts
|

A Mini-Review on Lichen-Based Nanoparticles and Their Applications as Antimicrobial Agents

Abstract: Biological entities such as green plants, fungi, and lichens are now a days persistently explored for the synthesis of nanoparticles. Lichen-based nanoparticles are also becoming increasingly popular owing to their biocompatibility, eco-friendliness, and cost-effectiveness. The lichen-based metal nanomaterials, particularly synthesized using green chemistry approaches, have turned out to be great substitutes to conventional antimicrobial therapies. Many scientific reports established the significant antimicrob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 23 publications
(41 reference statements)
0
6
0
Order By: Relevance
“…Diverse nanostructures such as lipid nanoparticles, nanoliposomes, nanomicelles, and carbon nanotubes or different delivery systems, including lactoferrin, can significantly increase the bioavailability, effectiveness, enhance stability, and improve pharmacokinetics of many compounds [68]. Lichen-based nanoparticles are also becoming increasingly popular owing to their biocompatibility, eco-friendliness, and cost-effectiveness [69]. The green synthesis of silver nanoparticles (AgNPs) is a method in which compounds from plants are used for the reduction of AgNO 3 instead of toxic chemicals.…”
Section: Future Challengesmentioning
confidence: 99%
See 1 more Smart Citation
“…Diverse nanostructures such as lipid nanoparticles, nanoliposomes, nanomicelles, and carbon nanotubes or different delivery systems, including lactoferrin, can significantly increase the bioavailability, effectiveness, enhance stability, and improve pharmacokinetics of many compounds [68]. Lichen-based nanoparticles are also becoming increasingly popular owing to their biocompatibility, eco-friendliness, and cost-effectiveness [69]. The green synthesis of silver nanoparticles (AgNPs) is a method in which compounds from plants are used for the reduction of AgNO 3 instead of toxic chemicals.…”
Section: Future Challengesmentioning
confidence: 99%
“…Many other reports have described the synthesis of nanoparticles from various types of lichens [72][73][74][75][76]. For the list of publications on lichen-based nanoparticles see the review by Rattan et al [69]. However, none of these nanoparticles have been tested in an in vivo cancer model.…”
Section: Future Challengesmentioning
confidence: 99%
“…Most of these employ extracts of different plant parts such as seeds, leaves, flowers, etc. [ 11 , 16 , 17 ], but animal blood serum [ 18 ], invertebrates [ 19 ], algae [ 20 ], lichens [ 21 ], fungi [ 22 ], and bacteria [ 11 , 23 , 24 ] have been used as well. Different organisms may provide different physicochemical characteristics and biological properties to the nanoparticles.…”
Section: Introductionmentioning
confidence: 99%
“…Lichen cells contain many types of secondary metabolites and other bioactive molecules, rendering them valuable for industrial, pharmaceutical, biotechnological, medical, and cosmetics applications [35]. Some researchers have demonstrated the potentiality of different species of lichens to fabricate unique NPs with different shapes, sizes, and physicochemical and biological activities [36]. Rattan et al demonstrated the role of different lichen species to synthe-size different types of NMs and their potentiality to act as promising antimicrobial agents [36].…”
Section: Introductionmentioning
confidence: 99%
“…Some researchers have demonstrated the potentiality of different species of lichens to fabricate unique NPs with different shapes, sizes, and physicochemical and biological activities [36]. Rattan et al demonstrated the role of different lichen species to synthe-size different types of NMs and their potentiality to act as promising antimicrobial agents [36]. Alqahtani et al reported that methanolic extracts of two lichen species, Xanthoria parietina and Flavopunctelia flaventior, were recently shown to have the po-tential to reduce silver nitrate into Ag-NPs extracellularly [37].…”
Section: Introductionmentioning
confidence: 99%